Radical frame semantics and biblical Hebrew : exploring lexical semantics - Shead, Stephen L. (Leiden ; Boston : Brill, 2011)
Drawing on various modern linguistic models, including cognitive linguistics, frame semantics, and construction grammar, this book presents a new, integrated approach to lexical semantic analysis of biblical Hebrew, applying it in a detailed study of words related to "exploring."
pt. 1. Foundations for lexical semantics -- pt. 2. Critiquing and enhancing framenet -- pt. 3. Frame semantics and biblical Hebrew.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 630
Keywords: Bible. -- Language, style; Bible; Hebrew language -- Semantics; Hebrew language -- Lexicology; FOREIGN LANGUAGE STUDY -- Hebrew; Hebrew language -- Lexicology; Hebrew language -- Semantics; Electronic books